Respuesta :
Step-by-step explanation:
Let's solve your equation step-by-step.
3(2x+1)+4=10
Step 1: Simplify both sides of the equation.
3(2x+1)+4=10
(3)(2x)+(3)(1)+4=10(Distribute)
6x+3+4=10
(6x)+(3+4)=10(Combine Like Terms)
6x+7=10
6x+7=10
Step 2: Subtract 7 from both sides.
6x+7−7=10−7
6x=3
Step 3: Divide both sides by 6.
6x/6=3/6
x=1/2
Answer:
x=1/2
Answer:
x = 1/2
Step-by-step explanation:
3(2x + 1) + 4 = 10
open the parenthesis
3 * 2x + 3 * 1 + 4 = 10
6x + 3 +4 = 10
6x + 7 = 10
subtract 7 from both sides of the equation
6x + 7 - 7 = 10 - 7
6x = 10 - 7
6x = 3
divide both sides of the equation by 6
6x/6 = 3/6
x = 3/6
simplify the fraction
x = 1/2